Istratijiyat Muqtarahah li Ta’limil Lughah al-Arabiyyah ‘an Bu’d - Fajar Hidayat; Maslamah; Mohammad Abdul Khaliq Hasan (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2022)
هدف هذه الدراسة إلى معرفة الاستراتيجية المقترحة لتعليم اللغة العربية عن بعد بشكل عام، ومعرفة كيفية إجراءها في المراحل الثلاثة؛ المرحلة ما قبل التدريس والمرحلة أثناء التدريس والمرحلة ما بعد التدريس. استخدم الباحث في إنتاج هذا البحث منهج البحث المكتبي، وهي الأبحاث التي تجرى مكتبيا معتمدة فقط على البيانات والمعلومات المتاحة المنشورة. ولقد توصل الباحث من خلال هذا البحث على النتيجتين أولاهما تصور عام للاستراتيجية المقترحة في تعليم اللغة العربية عن بعد، وهذه الاستراتيجية تتمثل بتقديم المواد الدراسية المراد تعليمها لدى الدارسين عن طريق إعدادها بشكل مقاطع الفيديو، وثانيتهما كيفية إجراء هذه الاستراتيجيات في ثلاث مراحل مختلفة؛ الأولى مرحلة ما قبل التدريس وهي مرحلة إعداد الدروس مرحلة التحضير، والثانية مرحلة أثناء التدريس وهي مرحلة عرض الدروس، والثالثة مرحلة ما بعد التدريس وهي مرحلة تقويم عملية التدريس This study aims to know the proposed strategy for teaching the Arabic language remotely in general, and knowing how to perform it in the three stages; The pre-teaching stage, the in-teaching stage, and the post-teaching stage. In producing this research, the researcher used the desk research method, It is the research that is conducted in the office based only on the available published data and information. Through this research, the researcher reached two results, the first of which is a general conception of the proposed strategy in teaching Arabic at a distance, This strategy is to provide the study materials to be taught to the students by preparing them in the form of videos, and The second is how to conduct these strategies in three different phases; The first stage is the pre-teaching stage, which is the stage of preparing lessons, the stage of preparation, The second stage is during teaching, which is the stage of presenting lessons, The third stage is the post-teaching stage, which is the stage of evaluating the teaching process.